Perceptions of Decision-Making Roles and Priorities that Affect Rebuilding after Disaster: The Example of L'Aquila, Italy. Issue 3 (August 2013) - Liel, Abbie B.; Corotis, Ross B.; Camata, Guido; Sutton, Jeannette; Holtzman, Rose; Spacone, Enrico
This study examines decision making for recovery and reconstruction in L'Aquila, Italy, over the one-year period following the 6 April 2009 earthquake. The paper focuses on local and national perceptions of government response to the earthquake, community involvement in reconstruction decision processes, the establishment of rebuilding priorities, and prospects for future seismic risk reduction. Data were collected through 23 semi-structured, face-to-face key informant interviews with local leaders (including community, building industry, and government representatives) and 4 interviews with national leaders. Findings show that although local leaders were satisfied with the Department of Civil Protection's emergency response, there was frustration with funding and priorities for permanent rebuilding. Public involvement in decision making varied by community, but in most cases was limited, leading local leaders to express distrust in government and national leadership and their decisions. The case study also illustrates the importance of authority and resource coordination between the national and local levels.